Role of Natural Language Processing in Social Media - Andhare, Aditya; Thorat, Surabhi; Shaga, Vikrant (International Journal of Computer Sciences and Engineering, 2025)
This paper highlight role of Natural Language Processing in social media sources like twitter, Facebook, LinkedIn etc. As now a day’s social media playing the vital role in terms of current trends social issues awareness etc. The major area where social media analysis requires is business analytics. As every business need the customer reviews and preferences for their business growth. This paper explains the major steps involved in social media mining.